THE ART OF PATTERN CARVING OF THE TRUSS (DAUKEO) ON A WOODEN HOUSE STRUCTURAL SYSTEM IN HUE AND THU DAU MOT CITIES - Hieu, TD; ND, Ky (Proceeding of the International Conference on Arts and Humanities, 2023)
It can be said that the quintessence of wooden house architecture in Vietnam in general and in Hue and Thu Dau Mot cities, in particular, is reflected in the motifs of wood carving patterns in the interior. Especially the motifs are decorated on the Daukeo with various, diverse, highly artistic themes and show the characteristics of each house, as well as feel the aesthetic level of the house owner. From those values, the contents of the article focus on bringing out the artistic values ​​of this unique decoration in the architectural structure of wooden houses in these two localities. The author has carried out a survey and investigated nearly 200 details of Daukeo carving in wooden houses in a total of nearly 100 wooden houses to recognize and better understand the motifs of carving art on Daukeo in the architecture of traditional wooden houses and modern wooden houses. So to bring into play the architectural value have a national character that may be gradually lost, to find the core values, or to want to find the original form of the Daukeo, as well as the meaning of this art of wooden carving, contributes to preserving the delicate traditional patterns of the national culture in general and the beauty of the wooden house in particular.